Wykupy menedżerskie w kształtowaniu efektywności polskich przedsiębiorstw - Szczepankowski, Piotr (Managers' Buyouts in Shaping of Polish Enterprises Effectiveness, 2005)
The dynamic transformation of Polish economy is well advanced. However, the management buyout market has been slowly developed. The article analyses the role of management buyouts in efficiency creation of Polish enterprises. Managers taken over through MBOs substantially increase their return on equity (ROE) thanks to increased efficiency, higher debt leverage and better allocation of assets. On macroeconomic improvements, MBOs contribute to better allocation of capital and higher efficiency of the economy. MBOs can also be successfully used as a potent tool for acceleration of economic restructuring. In the article the results of interviews with managers who bought some Polish firms are presented. The interviews focused on motives, efficiency and barriers of MBOs in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 408-425